Use the formula \( f^{\prime}(x)=\lim _{z \rightarrow x} \frac{f(z)-f(x)}{z-x} \) to find the derivative of the following function \( \quad f(x)=\frac{4}{x+4} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To find the derivative of the function \( f(x) = \frac{4}{x+4} \) using the formula for the derivative, we start by substituting into the formula: \[ f^{\prime}(x) = \lim_{z \rightarrow x} \frac{f(z) - f(x)}{z - x} \] First, compute \( f(z) \): \[ f(z) = \frac{4}{z + 4} \] Now, compute \( f(z) - f(x) \): \[ f(z) - f(x) = \frac{4}{z + 4} - \frac{4}{x + 4} \] To combine these fractions, find a common denominator: \[ = \frac{4(x + 4) - 4(z + 4)}{(z + 4)(x + 4)} = \frac{4x + 16 - 4z - 16}{(z + 4)(x + 4)} = \frac{4x - 4z}{(z + 4)(x + 4)} = \frac{4(x - z)}{(z + 4)(x + 4)} \] Now substitute back into the limit: \[ f^{\prime}(x) = \lim_{z \rightarrow x} \frac{\frac{4(x - z)}{(z + 4)(x + 4)}}{z - x} \] This simplifies to: \[ = \lim_{z \rightarrow x} \frac{4(x - z)}{(z + 4)(x + 4)(z - x)} = \lim_{z \rightarrow x} \frac{-4}{(z + 4)(x + 4)} \] Because \( z - x = -(x - z) \). Now, as \( z \) approaches \( x \): \[ f^{\prime}(x) = -\frac{4}{(x + 4)(x + 4)} = -\frac{4}{(x + 4)^2} \] So the derivative is: \[ f^{\prime}(x) = -\frac{4}{(x + 4)^2} \]